Advancing One human–animal–environment Health for global health security: what does the evidence say?. Issue 10376 (18th February 2023) - Zinsstag, Jakob; Kaiser-Grolimund, Andrea; Heitz-Tokpa, Kathrin; Sreedharan, Rajesh; Lubroth, Juan; Caya, François; Stone, Matthew; Brown, Hannah; Bonfoh, Bassirou; Dobell, Emily; Morgan, Dilys; Homaira, Nusrat; et al.
Summary: In this Series paper, we review the contributions of One Health approaches (ie, at the human–animal–environment interface) to improve global health security across a range of health hazards and we summarise contemporary evidence of incremental benefits of a One Health approach. We assessed how One Health approaches were reported to the Food and Agricultural Organization of the UN, the World Organisation for Animal Health (WOAH, formerly OIE), and WHO, within the monitoring and assessment frameworks, including WHO International Health Regulations (2005) and WOAH Performance of Veterinary Services. We reviewed One Health theoretical foundations, methods, and case studies. Examples from joint health services and infrastructure, surveillance–response systems, surveillance of antimicrobial resistance, food safety and security, environmental hazards, water and sanitation, and zoonoses control clearly show incremental benefits of One Health approaches. One Health approaches appear to be most effective and sustainable in the prevention, preparedness, and early detection and investigation of evolving risks and hazards; the evidence base for their application is strongest in the control of endemic and neglected tropical diseases. For benefits to be maximised and extended, improved One Health operationalisation is needed by strengthening multisectoral coordination mechanisms at national, regional, and global levels.